A Concise Review on Contemporary and Novel Treatments Addressing the Prevention and Control of Hyperpigmentation - Onkar Nandraj, Jagdale; Gajanan, Khule Ashwini; Karande, Dr. K.M. (Asian Journal of Pharmaceutical Research and Development, 2024)
Hyperpigmentation is a common skin condition characterized by the darkening of certain areas of the skin due to an excess production of melanin. This condition can be caused by a variety of factors, including sun exposure, hormonal changes, inflammation, and skin injuries. Hyperpigmentation can have a significant impact on a person's self-esteem and quality of life. Hormonal changes, such as those experienced during pregnancy or menopause, can also lead to hyperpigmentation. Inflammation from conditions like acne or eczema can cause the skin to produce excess melanin, resulting in dark spots or patches. Additionally, skin injuries, such as cuts or burns, can trigger the body to produce more melanin as part of the healing process, leading to hyperpigmentation. Creams containing ingredients like hydroquinone, retinol, or vitamin C can help lighten dark spots and even out skin tone. Medications containing corticosteroids, may be recommended for more severe cases of hyperpigmentation. In addition, novel drug delivery systems such as liposomes, Transferosomes, Niosomes etc. have shown better penetration topically hence they can be used to treat pigmentation. Understanding the causes of hyperpigmentation and seeking appropriate treatment can help improve the overall health and appearance of the skin. By addressing the underlying factors contributing to hyperpigmentation and using targeted skincare products or treatments, individuals can achieve a more even complexion and feel more confident in their skin. Background: The topic of hyperpigmentation is of significant interest in dermatology and cosmetology due to its widespread prevalence and impact on individuals' skin health and appearance.several traditional treatments such as topical hydroquinone and retinoids have been utilized for managing hyperpigmentation, there is an increasing recognition of the need for more effective and targeted intervention.